The Fintech Phenomenon: Protection of Consumer Privacy Data in Online Lending - Dewi Sartika Saimima , Ika; Gola Patria , Valentino (Jurnal Kajian Ilmiah, 2021)
Abstract Financial technology innovation that occurs nowadays leads to accelerated changes in the financial sector. However, these developments are like double-edged swords, on the one hand they provide convenience for consumers, on the other hand pose risks for consumers related to the confidentiality of their personal data. Money lending business through Peer to Peer lending (P2P lending) system often results in consumers receiving threats when they are late making payments. This paper presents several cases that result in consumers experiencing personal data theft, receiving threats directed at relatives or acquaintances. Even committing fraud by taking money from borrowers or customers without following the regulations made by the Financial Services Authority (OJK). The research data is carried out in a qualitative normative way where the data is translated based on legal norms and uses legal theory that can explain and answer existing legal problems. Keywords: Consumer Protection, Peer to Peer lending (P2P lending), Private Data Protection Abstrak Inovasi teknologi keuangan yang terjadi saat ini mengarah pada akselerasi perubahan di sektor keuangan. Namun perkembangan tersebut ibarat pedang bermata dua, di satu sisi memberikan kemudahan bagi konsumen, di sisi lain menimbulkan risiko bagi konsumen terkait kerahasiaan data pribadinya. Bisnis money lending melalui sistem Peer to Peer lending (P2P lending) seringkali mengakibatkan konsumen mendapat ancaman ketika mereka terlambat melakukan pembayaran. Makalah ini menyajikan beberapa kasus yang mengakibatkan konsumen mengalami pencurian data pribadi, menerima ancaman yang ditujukan kepada kerabat atau kenalan. Bahkan melakukan penipuan dengan mengambil uang dari debitur atau nasabah tanpa mengikuti ketentuan Otoritas Jasa Keuangan (OJK). Data penelitian dilakukan secara normatif kualitatif dimana datanya diterjemahkan berdasarkan norma hukum dan menggunakan teori hukum yang dapat menjelaskan dan menjawab permasalahan hukum yang ada. Kata kunci: Peer to Peer lending (P2P lending), Perlindungan Konsumen, Perlindungan Data Pribadi Kata Kunci: Perlindungan Konsumen, Peer to Peer lending (P2P lending), Perlindungan Data Pribadi